Overview of Inflammatory and Coagulation Markers in Elderly Patients with COVID-19: Retrospective Analysis of Laboratory Results - Corina Popazu; Aurelia Romila; Marius Petrea; Robert Marius Grosu; Alina-Maria Lescai; Adriana Liliana Vlad; Violeta Diana Oprea; Alexia Anastasia Ștefania Baltă (Life)
Background: Elderly patients with COVID-19 often exhibit a complex interplay between hypercoagulability and coagulopathy, key factors in determining the risk of severe complications and mortality. This study aimed to analyze coagulation and inflammatory markers to identify critical predictors of adverse outcomes in this vulnerable population. Material and Methods: The retrospective study was conducted on a sample of 1429 elderly patients (≥60 years) diagnosed with COVID-19, hospitalized in “Sf. Ap. Andrei” St. Apostle Andrew’s County Emergency Hospital in various wards between March 2020 and August 2022. Data were collected from medical records and included inflammatory markers (C-reactive protein, procalcitonin, ESR) and coagulation markers (prothrombin time, INR, fibrinogen, D-dimer). The SPSS 2.0 statistical software was used to conduct the study. Results:Coagulation markers: Prothrombin activity averaged 74.22%, below normal levels, indicating a heightened bleeding risk, while fibrinogen levels were significantly elevated (mean: 531.69 mg/dL), reflecting hypercoagulability. Prolonged prothrombin time (mean: 17.28 s) and elevated INR (International normalized ratio) (mean: 1.51) were associated with increased mortality, emphasizing their role in risk stratification. Elevated D-dimer levels (mean: 2.75 mg/L) further highlighted thromboembolic risks. Inflammatory markers: C-reactive protein (CRP) and erythrocyte sedimentation rate (ESR) showed marked elevations (mean CRP: 92.09 mg/L, mean ESR: 58.47 mm/h), correlating with heightened systemic inflammation and poor outcomes. Bacterial infections: Elevated procalcitonin (mean: 1.98 ng/mL) suggested secondary bacterial infections, particularly in mechanically ventilated patients, significantly worsening prognosis. Conclusions: The duality of hypercoagulability and coagulopathy in elderly COVID-19 patients underscores the importance of consistently monitoring coagulation markers such as prothrombin time, INR, D-dimer, and fibrinogen. Simultaneously, elevated inflammatory markers and secondary bacterial infections require prompt therapeutic interventions. This study highlights the critical need for personalized management strategies to mitigate complications and reduce mortality in this high-risk population.